LOSS SEVERITY DISTRIBUTION ESTIMATION OF OPERATIONAL RISK USING GAUSSIAN MIXTURE MODEL FOR LOSS DISTRIBUTION APPROACH - Seli Siti Sholihat; Hendri Murfi (Jurnal Ilmiah Ekonomi Bisnis, 2017)
Banks must be able to manage all of banking risk; one of them is operational risk. Banks manage operational risk by calculates estimating operational risk which is known as the economic capital (EC). Loss Distribution Approach (LDA) is a popular method to estimate economic capital(EC).This paper propose Gaussian Mixture Model(GMM) for severity distribution estimation of  loss distribution approach(LDA). The result on this research is the value at EC of LDA method using GMM is smaller    2 % - 2, 8 % than the value at EC of LDA using existing distribution model. Keywords:  Loss Distribution Approach, Gaussian Mixture Model, Bayesian Information Criterion, Operational Risk.